Potential, Challenges, and Threats for the Application of New Breeding Techniques by the Private Plant Breeding Sector in the EU - Jorasch, Petra (Frontiers in Plant Science, 2020)
Reconciling sustainability with agricultural productivity in the face of climate change relies strongly on the development of resilient, high-yielding crops of superior nutritional value that can be grown more resource efficiently. Therefore, innovation in plant breeding has gained unprecedented importance. Plant breeding depends upon genetic variability within crops and their relatives as a basis for developing new plant varieties with improved characteristics. Plant breeders are continuously integrating the latest methods in plant biology and genetics into their breeding toolbox to more efficiently use existing diversity but also to induce new genetic variation. Over the past years ever more precise and efficient plant breeding methods have been developed. This plant breeding innovation leap is based on an in-depth understanding of plant genomes and refinement of breeding methods, enabling more efficient, more precise and faster progress in achieving the desired breeding goals. Consequently, these plant breeding innovations are rapidly being developed and utilized internationally and across the seed sector, public and private research, plant species and markets. The results of a survey among 62 private plant breeding companies conducted by Euroseeds and presented in this publication confirm the enormous interest of companies in using new breeding techniques (NBTs) for a wide range of crop species and traits and the negative impact of the current regulatory situation in the EU on companies’ decisions for investments in NBT-related R&D activities for the EU market and beyond.